Technostress Pada Mahasiswa Akuntansi Dan Kecurangan Akademik Selama Pandemi Covid-19 - Dhea Eucharisty Lumenta; Evi Maria (Jurnal Akuntansi Manado (JAIM), 2024)
This study aims to examine the influence of technostress on academic dishonesty among accounting students during the COVID-19 pandemic from the perspective of the theory of planned behavior. The research was conducted on accounting students at Universitas Satya Wacana using a questionnaire survey with 239 respondents. Linear regression analysis was used to analyze the data. The study's results found that the higher the level of technostress experienced by students, the greater the tendency for students to engage in academic dishonesty. This study provides empirical contributions on managing technostress to prevent academic dishonesty among students, particularly in online learning. These findings are expected to assist universities in designing more effective policies to reduce the pressures caused by technology usage, ensuring the academic integrity of accounting students is maintained.